2016
DOI: 10.1371/journal.pone.0144798
|View full text |Cite|
|
Sign up to set email alerts
|

Platoon Interactions and Real-World Traffic Simulation and Validation Based on the LWR-IM

Abstract: Platoon based traffic flow models form the underlying theoretical framework in traffic simulation tools. They are essentially important in facilitating efficient performance calculation and evaluation in urban traffic networks. For this purpose, a new platoon-based macroscopic model called the LWR-IM has been developed in [1]. Preliminary analytical validation conducted previously has proven the feasibility of the model. In this paper, the LWR-IM is further enhanced with algorithms that describe platoon intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Previous works had validated the application of the LWR‐IM on the system in Fig. 8 revealed that simulations based on the LWR‐IM closely resemble the real world [23, 24]. Hence, the comparison of the INT‐CONTROL timing plans and existing FT timing plans can be compared using simulations by setting certain ‘test’ scenario.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous works had validated the application of the LWR‐IM on the system in Fig. 8 revealed that simulations based on the LWR‐IM closely resemble the real world [23, 24]. Hence, the comparison of the INT‐CONTROL timing plans and existing FT timing plans can be compared using simulations by setting certain ‘test’ scenario.…”
Section: Methodsmentioning
confidence: 97%
“…1, the NET‐PREDICT utilises measured data from traffic detectors (or simulated inputs) to provide network‐wide predictions of platoon dynamics such as platoon flow, platoon sizes, arrival time, and queues for a future time horizon. All predictions are based on the LWR‐IM traffic model that could enable the estimation of platoon size, arrival time, and estimates performances of queues [23, 24]. The functions of the NET‐PREDICT are further explained in Section 3.1.…”
Section: Extension To the Utnsimmentioning
confidence: 99%
See 2 more Smart Citations
“…After publication of this article [ 1 ], concerns were raised about similarities of this work to previously published articles [ 2 6 ], reuse of equations and figures from those articles, and whether these related works were sufficiently discussed in the article so as to place the new work in the PLOS ONE article [ 1 ] into context.…”
Section: Notice Of Republicationmentioning
confidence: 99%